Challenges and Opportunities in the Implementation of Islamic Religious Education Curriculum in Pesantren- Based Schools - Albert, Hugo (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2021)
Islamic religious education (IRE) holds significant importance in the curriculum of pesantren-based schools, reflecting the integration of religious teachings with academic subjects. This study explores the challenges and opportunities in implementing the IRE curriculum within the context of pesantren- based educational institutions. Employing qualitative methods, including literature review and library research, this paper examines the multifaceted aspects shaping the implementation of the IRE curriculum. The analysis reveals various challenges encountered, such as curriculum alignment with national educational standards, teacher qualification and training, pedagogical approaches, and resource limitations. Additionally, the study uncovers opportunities present in the integration of technology, community engagement, and partnerships with governmental and non- governmental organizations to enhance the effectiveness of IRE curriculum delivery. By addressing these challenges and leveraging available opportunities, pesantren- based schools can better navigate the complexities of implementing the IRE curriculum and foster holistic Islamic education for students.